MELESTARIKAN BUDAYA TARI KEPADA MASYARAKAT DALAM PERINGATAN HARI TARI DUNIA MELALUI EVENT SOLO MENARI 2025: PRESPEKTIF PENDIDIKAN KARAKTER. - Salsabelia Ainaning, Nariswari; Suyahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the functions of the Solo Menari 2025 event and the challenges faced in introducing dance culture to the community while instilling character education values to celebrate World Dance Day. The research method applied is descriptive qualitative. The study was conducted in Surakarta at the Solo Menari 2025 event, with research subjects comprising participating dancers, event organizers, and the general public attending the event. Meanwhile, the research object focuses on the functions of Solo Menari 2025 in preserving dance culture and instilling character values, as well as the challenges encountered. Data collection techniques include interviews, literature analysis, and field observations. The research findings indicate that Solo Menari 2025 not only serves as a platform for preserving traditional dance arts but also successfully instills character values such as discipline, responsibility, self-confidence, tolerance, cooperation, patriotism, and orderliness. These values are internalized through practice sessions, performances, and social interactions between participants and the community. These results align with previous studies affirming that dance arts education can function as a comprehensive, relevant, and contextual means of character education. However, this study also identified several obstacles, including the event's frequency of only once a year, limited budget, transportation access issues, and competition from digital entertainment. Therefore, Solo Menari 2025 needs further development to become a sustainable medium for cultural preservation and character education. The implication of this study is the need to integrate dance arts into formal and non-formal education as an effort to preserve culture and build national character.